Size at birth, weight gain over the life course, and low-grade inflammation in young adulthood: northern Finland 1966 Birth Cohort study - Tzoulaki, Ioanna; Jarvelin, Marjo-Riitta; Hartikainen, Anna-Liisa; Leinonen, Maija; Pouta, Anneli; Paldanius, Mika; Ruokonen, Aimo; Canoy, Dexter; Sovio, Ulla; Saikku, Pekka; Elliott, Paul (European heart journal, 2008)
Low-grade inflammation might mediate associations between size at birth, early life growth, excessive weight gain, and subsequent risk of cardiovascular disease in adult life. Our aim was to investigate relationships between fetal growth, weight over the life course, and low-grade inflammation measured by serum high sensitivity C-reactive protein (CRP) levels at 31 years. General population-based northern Finland 1966 Birth Cohort study of 5840 participants attending a clinical examination at 31 years, including measurement of CRP. Weight and height were assessed at birth, 12 months, and 14 and 31 years of age. CRP levels at 31 years were 16% [95% confidence interval (CI) 8, 23] higher per 1 kg lower birth weight, 21% (95% CI 2, 37) higher per 10 cm lower birth length, and 24% (95% CI 10, 36) higher per 1 kg/m3 lower ponderal index, after adjustment for potential confounders. Participants with highest tertile body mass index (BMI) at 31 years and lowest tertile birth weight had the highest average CRP levels. Per unit increase in BMI from 14 to 31 years was associated with 16% (95% CI 14, 17) higher CRP levels; the association was larger for those in the top BMI tertile at age 14 years. Systemic low-grade inflammation may lie on the causal pathway that relates impaired fetal growth and weight gain from childhood to adulthood to adverse adult cardiovascular health. Lifestyle changes from early life might be an important step in reducing cardiovascular risk in adults.